Rancang Bangun Sistem Monitoring Cairan Pembersih Pada Robot Permbersih Kaca Berbasis Mikrokontroller Atmega8535 - Hadi, Herry Sufyan; Abdurrakhman, Arief; Haqqi Dudayef, Ahmad; Sampurno, Bambang; Rahmadiansah, Andi; Balisranislam, Balisranislam (J-Eltrik, 2019)
Development in surabaya were very fast. There were 105 buildings which in the care of glass used exertion conventional cleaners. It  caused many accidents caused by the height of building. To solve this problem, there was one of solution that can be done for example to replace the conventional energy with cleaner engine, like glass cleaning robot. Glass cleaning robot usually used cleaning fluid with cleaning cloth or cleaner. Consumption of cleaner fluid was noted to get the result of used cleaner fluid. Monitoring would be helpful If process of monitoring is be done automatically. This monitoring system used water level of detection sensors as how high the level of liquids on glass cleaner robot. Monitoring the level of glass cleaner robot is displayed on android. Display used bluetooth HC-05 modul. Testing result was got that  average amounting were 0.065556 correction, and value of measuring uncertainty were ±0.120015678 with levels of trust 95 %.